2020
DOI: 10.3390/nu12041147
|View full text |Cite
|
Sign up to set email alerts
|

The Different Relationship between Homocysteine and Uric Acid Levels with Respect to the MTHFR C677T Polymorphism According to Gender in Patients with Cognitive Impairment

Abstract: In an elderly population with cognitive impairment, we investigated the association between serum uric acid (sUA) and serum homocysteine (sHcy), known risk factors for cerebrovascular disease. We also investigated the potential effect of the C677T polymorphism in the gene encoding methylenetetrahydrofolate reductase (MTHFR) to the sUA level in different dementia types. Participants underwent a battery of tests including measurements of sUA, sHcy, folic acid, and vitamin B12 as well as genotyping of the MTHFR l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
(77 reference statements)
2
9
0
Order By: Relevance
“…The association between uric acid and serum homocysteine can be explained by hydrolysis of S-adenosyl homocysteine leading to the formation of homocysteine and adenosine, because adenosine is degraded to form uric acid as its end-product (32). In the previous studies, the positive correlation between homocysteine and serum uric acid were observed (33)(34)(35), our results are consistent with these studies. However, there are also previous papers which reported that no correlations were found between serum homocysteine and serum uric acid in patients with gout or with uric acid-lowering treatment (36,37).…”
Section: Discussionsupporting
confidence: 92%
“…The association between uric acid and serum homocysteine can be explained by hydrolysis of S-adenosyl homocysteine leading to the formation of homocysteine and adenosine, because adenosine is degraded to form uric acid as its end-product (32). In the previous studies, the positive correlation between homocysteine and serum uric acid were observed (33)(34)(35), our results are consistent with these studies. However, there are also previous papers which reported that no correlations were found between serum homocysteine and serum uric acid in patients with gout or with uric acid-lowering treatment (36,37).…”
Section: Discussionsupporting
confidence: 92%
“…The study by Kim et al . [11] also found that the serum SUA was higher in subjects with hyperhomocysteinemia in an elderly population with cognitive impairment[11]. However, for patients with hypertension, there are few studies on the correlation between SUA and homocysteine.…”
Section: Resultsmentioning
confidence: 99%
“…The study of Kim et al . [11] found that serum SUA was higher in subjects with hyperhomocysteinemia in an elderly population with cognitive impairment. However, little attention has been paid to the correlation between SUA levels and hyperhomocysteinemia in patients with hypertension, and the relationship between SUA level and hyperhomocysteinemia remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These inconsistencies in the results may be due to different antipsychotic medications, methods of Hcy measurement, different phases of the disease, nutrient status, and ethnicity. Notably, sex differences in Hcy levels were found in patients with schizophrenia, and also in patients with bipolar disorders [43], and Alzheimer's dementia [44]. However, the exact etiological mechanism underlying the discrepancy in Hcy levels between males and females remains unclear.…”
Section: Discussionmentioning
confidence: 99%